1988
DOI: 10.2527/jas1988.6681877x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lasalocid on Reproductive Performance and Subsequent Lactation in the Sow

Abstract: The effect of lasalocid (140 mg . head-1 . d-1) on sow reproductive performance and subsequent piglet performance during lactation were examined in a trial that involved 114 sows. Treatments consisted of 1) control diet with no lasalocid during gestation and lactation; 2) lasalocid diet during gestation, control diet during lactation; 3) control diet during gestation and lasalocid diet during lactation; and 4) lasalocid diet during gestation and lactation. The addition of lasalocid either to gestation or lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This could possibly result in an improvement in the general condition of the In our study, this possible improvement in food efficiency did not significantly affect variations in weight of the sows and food consumption. Using lasalocid, Haydon and Hale (1988) and Holzgraefe et al (1986) did not obtain better results, and similarly, using tylosin, Mayrose et al (1962) did not obtain better results. Using salinomycin Bane et al (1990) found a smaller weight loss, though not statistically significant.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This could possibly result in an improvement in the general condition of the In our study, this possible improvement in food efficiency did not significantly affect variations in weight of the sows and food consumption. Using lasalocid, Haydon and Hale (1988) and Holzgraefe et al (1986) did not obtain better results, and similarly, using tylosin, Mayrose et al (1962) did not obtain better results. Using salinomycin Bane et al (1990) found a smaller weight loss, though not statistically significant.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies conducted with different antibiotics added to the sow diet demonstrated improvement in piglet weight and numbers at weaning and it seems that the most frequent benefit ascribed to the use of this kind of treatment in the sow (Mayrose et al, 1962;Hsu et al, 1980;Ilori, 1984;Haydon and Hale, 1988;Kyriakis et al, 1992) is an improvement of milk quality. Also clear is the reduction of pre-weaning mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced annual replacement rate in sows receiving VM, though not statistically significant, is important, both from the viewpoint of sow health and for its economic value to the farmer. In a study with lasalocid, Haydon and Hale (1988) obtained significantly increased milk fat content and a tendency towards bigger litters and higher litter weight gains, though neither was significant. Ilori (1984) demonstrated improvement in sow weight gain and increased weight and number of piglets weaned, following treatment with a streptomycin/penicillin Means in one row with different superscript letters differ (P < 005).…”
Section: Discussionmentioning
confidence: 87%
“…lasalocid (Haydon and Hale, 1988), tylosin (Mayrose, Speer, McCall and Hays, 1962) and lincomycin (Hsu, Chen, Wung, Luchsinger and Fang, 1980) have been shown to improve sow and/or litter performance and a preliminary report on virginiamycin (VM) has been published (Kyriakis, Polizopoulou, Tsaltas, Mouzouras, Demade and Vassilopoulos, 1988). Several products e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of the diet of the sows with compounds that enhance performance, including some antibiotics, influences the energy and protein utilization of the feed. Lasalocid (Haydon and Hale, 1988), tylosin (Mayrose et al., 1962), lincomycin (Hsu et al., 1980), streptomycin and penicillin (Ilori, 1984) and recently virginiamycin (Kyriakis et al., 1992b; Kantas et al., 1998) seem to improve sow and/or litter performance.…”
Section: Introductionmentioning
confidence: 99%